2002
DOI: 10.1002/1521-379x(200208)54:8<338::aid-star338>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a RecombinantBacillus sp. TS-23 α-Amylase by Adsorption-Elution on Raw Starch

Abstract: A Bacillus sp. TS‐23 α‐amylase produced by recombinant Escherichia coli was adsorbed onto raw starch and the adsorbed enzyme was eluted with maltose or maltodextrin in 50 mM Tris/HCl buffer (pH 8.5). The adsorption‐elution procedure resulted in a yield of 53% α‐amylase activity and sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS/PAGE) analysis showed that the eluted α‐amylase had a molecular mass of approximately 64 kDa. Raw starch could be used repeatedly in the adsorption‐ elution cycle with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, amylase activity was increased 34% by PMSF (3 mM) whereas urea diminished the enzyme activity to 43% 26 have reported an activity of 97% when using 10 mM PMSF, during incubation with Bacillus sp. TS‐23 α‐amylase produced by recombinant Escherichia coli .…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, amylase activity was increased 34% by PMSF (3 mM) whereas urea diminished the enzyme activity to 43% 26 have reported an activity of 97% when using 10 mM PMSF, during incubation with Bacillus sp. TS‐23 α‐amylase produced by recombinant Escherichia coli .…”
Section: Resultsmentioning
confidence: 98%
“…During the elution stage, the addition of d ‐glucose in the elution buffer enabled further precipitation by complexing with glucoamylase. This could be due to the presence specific binding sites on the enzyme for both the substrate (insoluble), as well as the soluble ligands . The purification strategy of starch affinity chromatography was employed by many researchers .…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial glucoamylase in the present study was purified by starch adsorption and gel filtration chromatography which revealed 40.02% yield with 2.73-fold and specific activity of 2300.5 (U/mg). During the elution stage, the addition of D-glucose in the elution buffer enabled further [29]. The purification strategy of starch affinity chromatography was employed by many researchers [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that recombinant a-amylase of Bacillus sp. strain TS-23 can be recovered from crude E. coli extract by adsorption to starch granules followed by gentle elution with a Tris-HCl buffer [11]. The conditions for recovery of chimeric proteins from starch, however, remain to be optimized.…”
Section: Adsorption Of Lapsbd To Raw Starchmentioning
confidence: 99%